Manajemen Strategi Implementasi Iklim Madrasah yang Bermutu Dalam Pendidikan Islam di Indonesia - Marjoni Marjoni (LPPM Institut Pesantren KH. Abdul Chalim, 2022)
The transformation of madrasa management to create a quality madrasa climate has its own challenges during the Covid-19 pandemic. This study aims to determine the madrasa management strategy to create a quality madrasa climate to improve the quality of Islamic education during the Covid-19 disruption in Indonesia. The research method used is a mixed method, namely by combining quantitative data and qualitative data. Quantitative data is in the form of a percentage of the application of the madrasa climate. Qualitative data in the form of a description of respondents' opinions about the use of madrasa climate. The respondents in this study were the head of the madrasa, educators, and employees who were in the madrasa environment, totaling 68 respondents. Researchers analyzed quantitative data from the questionnaire results descriptively. Meanwhile, qualitative data analysis was analyzed using the Miles & Huberman model. The results of this study indicate that strategy to create a quality madrasa climate as many as 89.7% of madrasas implementing this madrasa climate strategy aimed at improving the quality of education services. 83.8% of madrasas have their own characteristics in forming a positive madrasa climate such as, creating an Islamic culture, training, and developing the interests and talents of students, and emphasizing character education. This strategy is made based on the power of the principal who is assisted by educators, employees, and students well. This is indicated by the percentages of 92%, 92.6%, and 85.3%, respectively.